CORPORATE GOVERNANCE AND PRIVATIZATION IN SELECTED COUNTRIES IN TRANSITION - Marin, Slobodan; Šušić, Milan; Nikolić, Nikola (Journal of process management and new technologies, 2020)
Research on improvements  effectiveness of corporate governance mechanisms is a very complex research topic in the field of corporate governance, as well as strategic management. Different theoretical models and empirical results indicate the interdependence of corporate governance mechanisms and procedures within strategic decision-making. However, tradition and research to date indicate that a range of different approaches to corporate governance are evolving around the world. In practice, it is known that there is no single and always optimal choice of corporate governance model, as it depends on legal regulations, institutional frameworks and traditions of the country. However, all of them have in common that there is a high priority that works to increase the interest of shareholders in company, that the shareholders' funds can be used efficiently and wisely.Practice has shown that the regulatory and legal framework of most countries in transition did not have enough time to develop and adapt to the needs of privatization, which significantly affected its course and results. With progress in implementing reform processes, transition countries have constantly innovated privatization models. At the same time, each of them has developed a relatively specific model of property transformation, in accordance with the characteristics of the economy and the political situation. The importance of the privatization process in transition countries is reflected in increasing the efficiency of the economy, building the foundations for the introduction of a market economy and increasing government revenues.The main goal of the research, in this paper, is to analyze the results of the privatization process so far, emphasizing the advantages and disadvantages of this process, ie pointing out the positive experiences and key limitations with which countries in transition were faced during the implementation of the privatization process, which influenced the profiling of their business environment.